ARTIFICIAL INTELLIGENCE BASED AUTOGATE SYSTEM DEVELOPMENT CONCEPT IN IMMIGRATION EXAMINATION FOR INDONESIAN CITIZENS AT IMMIGRATION EXAMINATION IN SOEKARNO-HATTA INTERNATIONAL AIRPORT - Ary Rezqy Hakim (Polteknik Imigrasi, 2019)
Immigration checks are one part of the immigration control function which has a strategic role in maintaining security and upholding the country's sovereignty. Along with the times, the implementation of immigration checks has experienced several increasingly complex obstacles and challenges. The use of technology is seen as one of the solutions that can overcome these obstacles and challenges. The Directorate General of Immigration has currently implemented an innovation in the form of autogate which is considered to have provided various benefits, although from the beginning of its implementation, until now autogate has not been able to fully replace the role of immigration officers. This is because immigration checks using autogate are unable to carry out profiling, and interviews with prospective passers at the Immigration Checkpoint, but currently with the discovery of technology in the form of Artificial Intelligence, it is expected to be able to improve the quality of immigration checks with autogate.